Perancangan dan Pembuatan Vessel dengan Double Cylinder pada Unit Electric Road Sweeper - Ikhsan, Ridha; Sugiyanto, Sugiyanto; Ismail , Andhi Akhmad; Kuncoroadi , Robertus Tirta (Department of Mechanical Engineering, Vocational College, Gadjah Mada University., 2024)
The electric road sweeper developed by the Mechanical Engineering Department of the Gadjah Mada University Vocational School can handle waste management problems. To improve sweeper performance, several changes are still required in the unit, especially in the sweeper vessel section. In an effort to improve sweeper performance, vessel design is needed. Design and performance analysis of vessels using Autodesk Inventor software. In this research, the addition and replacement of hydraulic cylinder types was carried out to make it a transport vehicle. Apart from that, the use of lighter materials also reduces the weight of the vessel from 650 kg to 278.95 kg. The simulation results show that all vessel sweeper components have a safety factor above one, indicating that they are safe to use. Apart from that, this design is able to withstand loads of up to 4900 N without exceeding the yield strength limit of the material used by the vessel. The maximum inclination of the sweeper vessel is 30.4 degrees. Hydraulic cylinder testing shows an extend speed of 11.77 m/s and a retract speed of 7.9 m/s. Under 100 kg load conditions, the extend speed becomes 12.49 m/s and the retract becomes 8.39 m/s, the retract movement is faster due to gravity.